The Meanings Attributed to Kahramanmaraş Earthquakes - Emre, Yusuf; Yalçın, Yüsra (Ankara University, 2024)
Natural disasters are one of the important problems that threaten human life. In order to survive, it is important that people learn to live in harmony with these challenges. One of the natural disasters that negatively affect life is earthquakes. These earthquakes, which occur without the knowledge of people, have more or less effects on the people who experience them personally. People’s experiences in the face of earthquakes, the meanings they attribute to it and how they cope with this difficulty are a matter of curiosity. In this study, the meanings attributed to the earthquake by people who experienced the Kahramanmaraş earthquake were investigated. It was wondered whether the meanings that individuals attributed to the earthquake had religious or non-religious references. In particular, the study focussed on how participants from different age groups produced meaning in this regard. Phenomenology method, one of the qualitative research designs, was utilized and the data of the study were collected through semi-structured interviews. The research data were coded through predetermined categories and themes through descriptive analysis. According to the findings of the study, it was determined that older participants attributed more religious meaning to the earthquake than younger participants in many categories. It was observed that they referred to the afterlife by using religious references in both the cause of the earthquake and the coping category. Younger participants attributed more naturalistic meanings to the earthquake. © 2024, Ankara University. All rights reserved.
Kahramanmaraş Depremlerine Yüklenen Anlamlar
Keywords: Coping; Earthquake; Kahramanmaraş; Meaning; Psychology of Religion